Fluorinated Sulfilimino Iminiums: Efficient and Versatile Sources of Perfluoroalkyl Radicals under Photoredox Catalysis. (2nd March 2017) - Daniel, Marion; Dagousset, Guillaume; Diter, Patrick; Klein, Pierre‐André; Tuccio, Béatrice; Goncalves, Anne‐Marie; Masson, Géraldine; Magnier, Emmanuel
Abstract: Reported herein is the use of S‐perfluoroalkyl sulfilimino iminiums as a new source of RF radicals under visible‐light photoredox catalysis (RF =CF3, C4 F9, CF2 Br, CFCl2 ). These shelf‐stable perfluoroalkyl reagents, readily prepared on gram scale from the corresponding sulfoxide using a one‐pot procedure, allow the efficient photoredox‐induced oxyperfluoroalkylation of various alkenes using fac‐Ir(ppy)3 as the photocatalyst. Importantly, spin‐trapping/electron paramagnetic resonance experiments were carried out to characterize all the radical intermediates involved in this radical/cationic process.